ENHANCING COGNITIVE LEARNING OUTCOMES ON CARBOXYLIC ACIDS THROUGH NEARPOD-ASSISTED PROBLEM-BASED LEARNING: A STUDY IN ORGANIC CHEMISTRY COURSE - Nurlatipah, Dede Dalpa; Windayani, Neneng; Sari, Sari; Sukmawardani, Yulia (Chimica Didactica Acta, 2025)
This study aims to investigate the enhancement of students cognitive learning outcomes through the integration of Nearpod-assisted Problem-Based Learning (PBL) in carboxylic acid material, as well as to describe students activities, their ability to complete worksheets, and their responses to the use of this media. This study employed a pre-experimental method with a one-group pretest-posttest design and involved 48 fourth-semester students in the Organic Chemistry II course. The results indicate that learning activities were carried out very well (88.76%), students ability to complete worksheets was also high (average score: 88), and cognitive learning outcomes improved moderately (N-Gain: 0.63), with the highest achievement at the analysis level (C4). A total of 98.3% of students responded positively to the use of Nearpod in learning. These findings indicate that integrating the PBL model and Nearpod is an innovative and effective approach to enhancing cognitive learning outcomes, active participation, conceptual understanding, and higher-order thinking skills while highlighting its potential to improve the quality of chemistry education, particularly on abstract topics.